2014
DOI: 10.1097/brs.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Heterotopic Ossification Associated With Cervical Artificial Disc Replacement

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…The development of clinically significant HO is reported in 0-33% of cases at 2 years after surgery 1,21,36,37 and has been implicated as a factor in the reduction of range of movement 24 , this is supported by our results ( Figure 6). The objectivity of HO measurement has come under scrutiny, Choi 38 suggested that 'the more you look, the more you see', and variability in measurement has also been linked to bias from conflicts of interest 2 ; many studies have formalized this by using the McAfee scale 14 .…”
Section: Movement Maintenance and Radiological Changessupporting
confidence: 88%
See 1 more Smart Citation
“…The development of clinically significant HO is reported in 0-33% of cases at 2 years after surgery 1,21,36,37 and has been implicated as a factor in the reduction of range of movement 24 , this is supported by our results ( Figure 6). The objectivity of HO measurement has come under scrutiny, Choi 38 suggested that 'the more you look, the more you see', and variability in measurement has also been linked to bias from conflicts of interest 2 ; many studies have formalized this by using the McAfee scale 14 .…”
Section: Movement Maintenance and Radiological Changessupporting
confidence: 88%
“…The development of which has been attributed to a number of factors, including natural progression of degeneration 20 , as well an iatrogenic causes 19,21,22 , which may be aggravated by reduced movement 23 . Disk replacements vary by material and design, which affect both motion preservation and wear and tear characteristics, and consequently the risk of HO development 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that this had no significant adverse effects on the clinical outcome parameters, as noted in other studies [27][28][29][30][31][32][33], efforts should be made to avoid the occurrence of HO.…”
Section: Adjacent Segment Degenerationmentioning
confidence: 90%
“…The appearance of HO right up to solid fusion (Grade 4) is a well known complication in cervical total disc replacement which can affect the motion, respectively, the function of the prosthesis [31,32,35] regardless the implant-type [7,11,17,27,28,[36][37][38][39]. The progression of HO into higher grades over time was also seen in other studies [28,32]. Up to now there is no study available that could demonstrate a significant effect of the use of NSAID in the early post-operative period to avoid or reduce the incidence of HO.…”
Section: Adjacent Segment Degenerationmentioning
confidence: 99%
“…In severe cases, HO limits range of motion, sometimes creating fusion of the segment. [16][17][18][19] Reported rates of HO following CTDR vary drastically, creating more debate and concern around the true rate and impact of HO. [20][21][22][23] The long-term effects of HO resulting in unintended fusion have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%